(untitled) (Research, Society and Development, 2021)
Children’s stories are important tools for cognitive development, formation of identity and values, in addition to strengthening the family bond, contributing to benefits related to the child’s development. The objective was to reflect on academic research that addresses the importance of pedagogical practices in the development of children with playfulness through children’s storytelling, considering their emotional and cognitive impact. The bibliographic research method was used, with a focus on the State of the Art and approaches, qualitative and quantitative. Whose analysis of the data sought to reflect on academic production about the importance of storytelling from early childhood, as an instrument for planning pedagogical practices, adding value and meaning to the child’s learning. Also evidencing the importance of the family in partnership with the school in this process of construction and encouragement for the practice of reading. The results demonstrate growing trends in quantities of publications, as well as it was found that the method used makes it possible to identify possibilities with effective learning results through storytelling. It is concluded that motor, emotional and cognitive aspects are built with pedagogical practices that use playfulness. In this way, children’s stories serve as a guide for pedagogical practices through playfulness in activities provided for the development of children’s skills.